The association of specific executive functions and falls risk in people with mild cognitive impairment and early-stage dementia - van der Wardt, Veronika; Logan, Phillipa A.; Hood, Victoria; Booth, Victoria; Masud, Tahir; Harwood, Rowan H. (Karger, 2015)
Background/Aims: